The Body as Instrument: John Glenn and the Evolution of NASA's Astronaut Health Standards, 1959–1998 - Moukthika Palla (Advanced International Journal for Research, 2026)
John Glenn’s two spaceflights highlight NASA’s shift from improvisational astronaut medicine to a rigorous, evidence‑based health standard. His 1962 Friendship 7 mission occurred when physicians “tested general robustness…rather than specific, known risks of microgravity,” reflecting the absence of human orbital data. By 1998, Glenn’s STS‑95 flight was designed as a targeted experiment comparing spaceflight‑induced physiological changes with natural aging—an idea he formed after noticing that microgravity effects “closely resembled the effects of ordinary human aging.” His experience bookends the development of NASA‑STD‑3001, showing how astronaut data transformed medical screening from broad endurance tests into defined, outcome‑based criteria that now guide crew health for future long‑duration missions.